Model Predicting the Risk of Endometrial Hyperplasia Developing into Endometrial Cancer - Su J; She L; Fan Y; Wang H; Zhang Q; Zhang J; Ma H (Dove Medical Press, 2024)
Jing Su,1,* Lina She,1,* Yang Fan,1 Honghong Wang,2 Qiaorui Zhang,1 Jiao Zhang,1 Hongyun Ma1 1Department of Obstetrics and Gynecology, People's Hospital of Ningxia Hui Autonomous Region, Ningxia Medical University, Yinchuan, People's Republic of China; 2Department of Pathology, People's Hospital of Ningxia Hui Autonomous Region, Ningxia Medical University, Yinchuan, People's Republic of China*These authors contributed equally to this workCorrespondence: Hongyun Ma, Department of Obstetrics and Gynecology, People's Hospital of Ningxia Hui Autonomous Region, Ningxia Medical University, No. 301, Zhengyuan North Street, Jinfeng District, Yinchuan, 750002, Ningxia, People's Republic of China, Tel +86-15378975354, Email mahongyun2021@163.comBackground: This study retrospectively analyzed the medical records of 200 patients with endometrial hyperplasia to predict the risk of concurrent endometrial cancer.Methods: Patients were categorized into either the endometrial cancer group or the endometrial hyperplasia group based on post-hysterectomy pathology. The investigation compared general information, tumor indices, fertility history, preoperative endometrial sampling methods, comorbidities, and clinical symptoms between the groups to identify risk factors for endometrial hyperplasia complicating endometrial cancer.Results: (1) Of the 200 patients, 68 (34.0%) were diagnosed with concurrent endometrial cancer post-hysterectomy. Among these, 60 (88.24%) had endometrioid adenocarcinoma, while 8 (11.76%) had other types. Stage I was identified in 58 patients (85.29%) and Stage II in 10 patients (14.71%). High differentiation was observed in 57 cases (83.82%), moderate differentiation in 7 cases (10.29%), and poor differentiation in 4 cases (5.89%), indicating that most endometrial cancers complicated by hyperplasia were early-stage, well-differentiated endometrioid carcinomas; (2) Univariate analysis revealed statistically significant differences in age, menopausal status, length of menopause, and preoperative endometrial pathology of severe atypical hyperplasia between the groups; (3) Multivariate analysis indicated significant differences for age ≥ 53.5 years (OR: 4.307, 95% CI: 2.018- 9.192, p < 0.05), menopausal status (OR: 5.250, 95% CI: 2.449- 11.252, p < 0.05), and severe atypical endometrial hyperplasia (OR: 4.817, 95% CI: 1.260- 18.419, p < 0.05); (4) Significant differences were observed among patients with endometrial hyperplasia when stratified by the presence of zero, one, two, or three high-risk factors.Conclusion: In conclusion, patients aged ≥ 53.5 years, those who are menopausal, and those with severe atypical endometrial hyperplasia preoperatively are at higher risk for endometrial cancer. The risk increases with the number of high-risk factors present in patients with atypical endometrial hyperplasia.Keywords: retrospective, endometrial hyperplasia, endometrial cancer, clinical features, high-risk factors, regression